Premature cardiovascular mortality and alcohol consumption before death in Arkhangelsk, Russia : an analysis of a consecutive series of forensic autopsies - Sidorenkov, Oleg; Nilssen, Odd-Ragnar; Nieboer, Evert; Grjibovski, Andrej; Kleshchinov, Nikolay (International Journal of Epidemiology, 2011)
This article is part of Oleg Sidorenkov's doctoral thesis available in Munin at http://hdl.handle.net/10037/3589 High CVD mortality among the middle-aged is a major cause of low life expectancy in Russia, especially among men. Hazardous alcohol consumption is suspected to be a powerful factor. All men (1099) and women (519) who died between 01.01.08 and 31.08.09 from cardiovascular disease at ages of 30-70 years in the city of Arkhangelsk, Northwest Russia, were included. CVD mortality was stratified by age, gender and diagnosis. For the cases diagnosed by forensic pathologists, the blood alcohol concentration (BAC) was determined. The forensic autopsy rate was 72% for men and 62% for women. The age-standardized CVD mortality rate (all age groups) in men was higher than in women. The largest male-to-female ratio (4.3) was observed in the age-group 50-59. Alcoholic and unspecified cardiomyopathies were the most dominant CVD mortalities in women, and second in men under fifty; they accounted for 50% and 25% of deaths, respectively. About one third of men and women who died from CVD under 60 had consumed alcohol shortly before death. This occurred most frequently among the diagnostic groups: “other acute or subacute cardiac ischemia”, “atherosclerotic heart disease” and “cardiomyopathies”. Alcohol was more likely to be found at autopsy in men than women (OR 1.55; 95% CI 1.14-2.10). No such difference was found for those who died from myocardial infarction, cerebrovascular diseases and cardiomyopathies. Less than 1% of the deceased had a BAC of 4g/l or higher. Alcohol consumption before death is an important correlate of premature CVD mortality in Northwest Russia, particularly among 50-59 year-old men. The largest gender difference in mortality, highest absolute number of premature CVD deaths, and the highest proportion of alcohol-positive autopsies occurred among them. Associations with alcohol consumption considerably vary between the types of CVD diagnoses, and this should be taken into account when planning ...